Vislumbres de Insubordinação Criativa manifestados por professores de Matemática em formação inicial na disciplina de Modelagem Matemática - Waideman, Adriele Carolini (2023)
This research, with a qualitative and interpretative approach, was carried out within the scope of the Mathematical Modeling (MM) discipline of a Mathematics Degree course at a public university in western Paraná. With a view to investigating manifestations of creative insubordination in the speeches and actions of Mathematics undergraduates when taking the subject, we sought to identify aspects with the potential to contribute to the initial training of teachers with a propensity for creative insubordination. To this end, initially, we carried out a mapping of the literature, in order to recognize, among other aspects, conditions and manifestations of Creative Insubordination highlighted by specialized literature. From the construction of a reference framework with four conditions and fifteen manifestations of Creative Insubordination, we analyzed the data produced in the discipline: audios, videos, reports, semi-structured interviews and class observations, many of them obtained remotely due to the pandemic. in which they happened. As results, the research revealed evidence of a glimpse of creative insubordination on the part of undergraduates resulting from their experiences in the MM discipline, as well as a critical awareness of the problems and limitations associated with the school environment and the classroom. We highlight that the discussions promoted within the scope of the Mathematical Modeling discipline, as planned, provided significant experiences as part of the initial training for future mathematics teachers. This allowed them to explore what was different, MM as a pedagogical practice, providing a broader perspective compared to the experiences they had during their career as students.